LATINA/OS AND THE MEDIA: A NATIONAL CATEGORY WITH TRANSNATIONAL IMPLICATIONS (Polifonia, 2014)
ABSTRACT: This essay focuses on the category of Latina/os, which was created in the United States to refer to the portion of the population with recent and/or historical roots in Latin America, and the love/hate or fear and desire relation of the US and Latina/os – desire of spectacular bodies and fear of working bodies – that is borne out by representations of Latina/os in mainstream media. The transnational circulation of these representations through popular culture expands their presence and meaning across the globe in ways that are unintended and deserve further study.KEYWORDS: Latina/os, media, representation RESUMO: Neste artigo, discuto a categoria latina/os, criada nos Estados Unidos para se referir à parcela da população com raízes recentes e/ou históricas na América Latina, e a relação amor/ódio ou medo e desejo entre os Estados Unidos e os latinos – desejo por corpos espetaculares e medo dos corpos trabalhadores –, corroborada por representações dos latinos na mídia convencional. A circulação transnacional dessas representações, por meio da cultura popular, expande sua presença e seus significados ao redor do planeta, de maneira nem sempre intencional, mas que deve/merece ser estudada.PALAVRAS-CHAVE: Latina/os, mídia, representação